2014
DOI: 10.3126/jpn.v4i7.10315
|View full text |Cite
|
Sign up to set email alerts
|

A study on microvascular density in breast carcinoma

Abstract: Background: Breast Cancer is the most frequent neoplasm causing death in women between 35-55 years of age. Of the Prognostic indicators existing for breast cancer, axillary lymph node status has been regarded as the most important one. Twenty to thirty percent of all lymph node negative patients will still develop a recurrence of the disease within 10 years of initial treatment. Therefore, a new prognostic marker that could identify patients at high risk of tumor recurrence more accurately than existing indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 15 publications
5
19
0
Order By: Relevance
“…This observation was similar to the previous studies (12,25,26) that were done on colorectal carcinoma, breast cancer and oral squamous cell carcinoma respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This observation was similar to the previous studies (12,25,26) that were done on colorectal carcinoma, breast cancer and oral squamous cell carcinoma respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The same result was obtained by Rofstad et al who reported that increased neo-angiogenesis in tumor tissues illustrated the direct spread to lymph nodes in cervical cancer (24). Such a correlation was reported by another study on breast cancer (25). By contrast, another study found no correlation between MVD and clinicopathologic variables (28).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[7] Pyakurel D et al, in his study concluded that MVD positively correlated with size of the tumour, lymph nodes with tumour grade and aggressiveness. [11] Teo et al showed that higher the microvessel densities in breast cancers, higher the risk of subsequent in situ cancer and invasive recurrence of previous in situ cancers with poorer response to treatment. [12] Majority of published reports have shown a significant correlation between the density of intratumoral micro vessels in invasive breast carcinoma and the incidence of metastasis and or survival.…”
Section: Discussionmentioning
confidence: 99%